A perspectiva de adolescentes sobre o cuidado da saúde mental e contribuições da Unidade Básica de Saúde (UBS) - Arenhart, Isis Fernanda (Universidade Federal de São Carlos, 2024)
The age period known as adolescence includes a wide range of experiences, depending on multiple factors such as the territory where one lives, income levels, race, ethnicity, gender, and more. Studies show that mental health problems such as depressive and anxious disorders, non-suicidal self-injury, self-harming behaviors, suicide ideation and attempts, and suicide itself have been increasing in this population. However, child and adolescent mental health policies are relatively recent. The Primary Health Care Service (Unidade Básica de Saúde - UBS), as a part of the Psychosocial Care Network, has the mission of promoting health and territorial care. This study aimed to identify the perspective of adolescents on mental health care and possible contributions of the UBS, to explore the strategies participants used for their own mental health care, to understand how they accessed mental health care activities at the UBS, and to identify their perspectives on the weaknesses and strengths of the UBS in providing this care. Eight adolescents aged 15 to 19 years (under 20), users of a UBS in a large municipality in the interior of São Paulo state, participated in the study. Semi-structured individual interviews were conducted with the adolescents, using a brief video as a prompt along with guiding questions. A report was created for each interview, sent to the respective participant for validation. The data were then fully transcribed, with participants anonymized using fictitious names, and underwent thematic analysis. The strategies for mental health care used by the participants involved talking about their feelings, psychological care at the UBS, engaging in pleasurable activities, and problem-solving and coping attitudes. Access to mental health care at the UBS was facilitated by the support of a responsible family member and/or referral from the school, with previous contact or connection with a UBS worker also serving as a facilitator. Participants identified several scientifically well-documented weaknesses in access to the UBS, including transportation difficulties, long waiting times for care, limited human resources, and concerns about privacy and confidentiality. They also mentioned a lack of information about the unit's offers and how to access them. Participants who accessed mental health care at the UBS had varied experiences with the unit's reception. Despite the waits, the free service was seen as a positive point, along with the existence of priority criteria for urgent situations and the non-judgmental attitude of the professionals. The study underscored the significance of developing mental health initiatives within the school environment. Access to community facilities (sports, leisure, and culture) was also pointed out as important for promoting mental health. The findings highlight the necessity for intersectoral collaboration, advocating for integrated service planning, as well as continuous training for health professionals and others who work with adolescents, especially those in education services, to be prepared to provide support on mental health issues.
La perspectiva de los adolescentes sobre el cuidado de la salud mental y las contribuciones del servicio de atención primaria de salud.
The perspective of adolescents on mental health care and contributions of the Primary Care Health Service
Keywords: Saúde do Adolescente; Atenção primária à saúde; Saúde mental; Promoção da saúde; Integralidade em saúde; Adolescent health; Primary health care; Mental health; Health promotion; Integrality in health; CIENCIAS DA SAUDE::SAUDE COLETIVA